2017
DOI: 10.1212/wnl.0000000000003770
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating cognitive impairment due to corticobasal degeneration and Alzheimer disease

Abstract: Objective: To identify clinical features that reliably differentiate individuals with cognitive impairment due to corticobasal degeneration (CBD) and Alzheimer disease (AD).Methods: Clinical features were compared between individuals with autopsy-proven CBD (n 5 17) and AD (n 5 16). All individuals presented with prominent cognitive complaints and were evaluated annually with semistructured interviews, detailed neurologic examinations, and neuropsychological testing. . Subsequent emergence of asymmetric motor/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 40 publications
1
24
0
3
Order By: Relevance
“…Although the number of patients with PSP/AD was small and Alzheimer's‐type pathology was relatively mild, we found no significant difference in frequency and severity of CI in PSP compared with PSP/AD. This is consistent with literature reporting CI in corticobasal degeneration; 59% of corticobasal degeneration had Alzheimer's‐type pathology, but it had minimal effect on the rate of dementia progression and dementia duration . Although it remains inconclusive, there was not enough evidence to suggest that Alzheimer's‐type pathology affected cognition in PSP‐CI.…”
Section: Discussionsupporting
confidence: 89%
“…Although the number of patients with PSP/AD was small and Alzheimer's‐type pathology was relatively mild, we found no significant difference in frequency and severity of CI in PSP compared with PSP/AD. This is consistent with literature reporting CI in corticobasal degeneration; 59% of corticobasal degeneration had Alzheimer's‐type pathology, but it had minimal effect on the rate of dementia progression and dementia duration . Although it remains inconclusive, there was not enough evidence to suggest that Alzheimer's‐type pathology affected cognition in PSP‐CI.…”
Section: Discussionsupporting
confidence: 89%
“…Driving behaviors were monitored for a median of 29 months (range, [21][22][23][24][25][26][27][28][29][30][31][32]. No accidents were reported by study participants or captured by the DRIVES.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all patients with Alzheimer’s disease, which includes familial AD and sporadic AD, have Aβ plaques deposited in brain tissue. Greater Aβ plaques accumulation also causes enhanced neuronal loss and leads to cognitive impairment [ 1 ]. Therefore, reducing the production of Aβ and promoting Aβ degradation have become one of ways to control the progression of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer’s disease (AD), a progressive neurodegenerative disorder, is already a major focus of research attention. AD causes functional impairment, like loss of cognitive functions and behavioral changes, which has severe effects on AD patients [ 1 , 2 ]. It was reported that over 46 million elderly people have cognitive impairment and memory loss caused by AD [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%